Justifying business intelligence systems adoption: a literature review on healthcare supply chain perspective / Nur Syahidah Wong Abdullah ... [et al.] - Wong, Nur Syahidah Abdullah; Ambad, Sylvia @ Nabila Azwa; Nordin, Sakka; Andrew, Jasmine Vivienne; Karen, Esther Tan (Universiti Teknologi MARA, Perlis, 2021)
Business Intelligence (BI) systems have played an essential position in facilitating information sharing, strategic cost-cutting, and improvement in business process management through data-driven decision-making analytics. The technological enablers of Industry 4.0 have empowered the clinician to attain accurate information in formulating predictive and data-driven diagnoses based on artificial intelligence-enabled medical devices resulting in an efficient and quality clinical pathway for patients. However, there is a noticeable distinction between the hospital's technological aptitude between clinician and non-clinician. The current technological capability of the hospital information system is to digitize daily business processes that could not offer intelligence reports for predicting, forecasting, and data-driven decision-making support. The compilation of past works of literature is expected to justify the need for the healthcare supply chain to adopt BI solutions that produce near real-time data in making efficient inventory management and procurement to support the clinician in delivering efficient and quality clinical pathways for patients by bringing the supplies at the right moment. Hence, a study of BI solutions in healthcare supply chain operation is achieved through a narrative overview of existing literature from papers published online. The results show that appropriate technological tools, resource competencies, and supplier management platform as the essential dimensions to support the business intelligence adoption effort. The study, therefore, not only identified the critical dimensions in facilitating BI adoption but also offer practical awareness to the healthcare policymakers to better understand the strategic need for BI systems in managing the entire hospital operations to gain a competitive advantage.